Studies on Sustainability Aspects of Building with Different Roofing Systems and Block Work - et. al., ZabahatShafiaKhanum, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today's world a massive amount of energy is used by the building industry. The non-renewable resources are increasingly being exhausted because of the intense use. Construction industry accounts for large quantities of greenhouse gas emissions which lead to climate change and ozone layer depletion. This adverse environmental impact stimulates the need for innovative construction strategies that reduce the overall carbon emissions and embodied energy that are represented. The study focused on a conventional building whose slab and block work is changed with different slab and block work and the embodied energy calculation of energy analysis, and the sustainability index and its different parameters that was compared with all the Green criteria recommended by SVAGRIHA a denotation for ‘Small Versatile Affordable Green Rating for Integrated Habitat Assessment’ council. It was found that the total construction of the Green building is more recommended in terms of environmental and ecological parameters. Semi Pro and Revit are used for them to calculate embodied energy and effective design respectively. A radar diagram has also been drawn to help with selecting the type of roofing and block work with respect to sustainability indicators.